Debt management in Brazil: Evaluation of the real plan and challanes ahead - Afonso S. Bevilaqua; Márcio Gomes Pinto Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1999)
The Brazilian domestic debt has posed two challenges to policy-makers: it has grown very fast and its maturity is extremely short. This has prompted fears that a default or a compulsory lengthening scheme would be imposed. Here, we analyze the domestic public debt management experience in Brazil, searching for policy prescriptions for the next few years. After briefly reviewing the recent domestic public debt history, we decompose the large rise in federal bonded debt during 1995-1998, searching for its macroeconomic causes. The main culprits are the extremely high interest payments–which were caused by the weak fiscal stance and the quasi-fixed exchange-rate regime, and the accumulation of assets of doubtful value, much of which may have to be written off in the future. Simulation exercises of the net debt path for the near future underscore the importance of a tighter fiscal stance to prevent the debt-GDP ratio from growing further. Given the need to quickly lengthen the debt maturity, our main policy advice is to foster and rely more on, inflation-linked bonds.
Keywords: E65; H63; 330